Correction: BTI-Tnao38, a new cell line derived from Trichoplusia ni, is permissive for AcMNPV infection and produces high levels of recombinant proteins - Hashimoto, Yoshi (BioMed Central, 2012)
After publication we discovered an error in the identification of the origin of the cell line reported in our article in BMC Biotechnology (2010, 10:50), entitled "Ao38, a new cell line from eggs of the black witch moth, Ascalapha odorata (Lepidoptera: Noctuidae), is permissive for AcMNPV infection and produces high levels of recombinant proteins". Upon analysis of primary A. odorata cultures, we found that they were contaminated with cells of Trichoplusia ni origin. The origin of the Ao38 cell line was determined as T. ni using three marker genes and the Ao38 cell line was renamed BTI-Tnao38. References to the origin of the cell line as Ascalapha odorata should be replaced with "a cell line of Trichoplusia ni origin". The absence of TNCL virus detection in the BTI-Tnao38 (Ao38) cell line was confirmed using a highly sensitive RT-PCR protocol capable of detecting TNCL virus RNA at approximately 0.018 copies/cell. Because of these observations, we have revised the title of the original article to "Correction: BTI-Tnao38, a new cell line derived from Trichoplusia ni, is permissive for AcMNPV infection and produces high levels of recombinant proteins" and two additional authors were added to reflect their contributions to the analysis of this cell line.